The Impact of Social Media Influencer on Consumer Purchase Behaviour toward MSME Food Vendors - Lina Budiarti; Agus Hermawan; Wening Patmi Rahayu (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The utilization of social media influencers has become a prevalent strategy for various organizations in this digital era, including Micro, Small, and Medium Enterprises. This study aims to analyze the role of social media influencer on consumer purchase behavior in the digital era. Using a quantitative approach, this study explores how influencer’s trustworthiness, attractiveness, experience, and content usefulness influence consumer purchase behavior. Data were collected by distributing 118 questionnaires to respondents consists of Indonesian culinary enthusiasts who engage with digital content produced by food influencer. Data analysis was performed using multiple linear regression. The results of this study indicate that influencer's trustworthiness, attractiveness, experience, and content usefulness have a positive and significant impact on purchasing behaviour both partially and simultaneously. This study provides managerial insights into how influencer marketing should be approached by companies. The findings emphasize that collaborating with social media influencer is essential as a strategic response to a highly contested market environment.